Peningkatan Kemampuan Membaca Memahami Teks Bahasa Jerman Melalui Metode Membaca Cepat - Allo, Monica Angelina Rante; Jufri, Jufri; Al-Ilmullah, Syarifah Fathimah (Academic : Journal of Social and Educational Studies, 2024)
Abstract. This study to improve the reading ability to understand German Texts of class XI SMA Negeri 12 Makassar using the fast reading method. This research is a classroom action research consisting of two cycle with each cycle consisting of planning, implementation, observation dan reflection stages. This research data consists of two types of data, namely qualitative data which is a description of the results of implementation and observation during the learning process dan quantitative data in the form of students improvement reading ability texts to understand texts in Cycle I and Cycle II. The average reading text score obtained by the students in Cycle I was 62.36 and in Cycle II the average value obtained by the students wa 83.06. The results showed that the speed reading method can improve the ability to reading German text of student in Class XI MIPA 6 SMA Negeri 12 Makassar.Keywords: Speed Reading Method, Reading Comprehension Ability, German Language Learning.